Co-prevalence of Epstein–Barr virus and high-risk human papillomaviruses in Syrian women with breast cancer. Issue 7 (2nd July 2016) - Al Moustafa, Ala-Eddin; Al-Antary, Noor; Aboulkassim, Tahar; Akil, Nizar; Batist, Gerald; Yasmeen, Amber
ABSTRAT: We recently performed 2 studies viewing the presence of Epstein–Barr virus (EBV) and high-risk human papillomaviruses (HPVs) types 16, 18, 31, 33 and 35 in human breast cancer in the Syrian population. Herein, we report that EBV and high-risk HPVs are co-present in breast cancer in Syrian women. Therefore, and based on our previous studies and present data, we reveal that 35 (32%) of 108 cancer samples are positive for both EBV and high-risk HPVs and their co-presence is associated with high grade invasive ductal carcinomas (IDCs) with at least one positive lymph nodes, in comparison with EBV and high-risk HPVs-positive samples, which are low to intermediate grade IDCs, respectively. Future studies are needed to confirm the co-presence and the cooperation effect of these onco-viruses in human breast carcinogenesis and metastasis.